Analisis Kompetensi Guru Madrasah Ibtidaiyah Dalam Pemanfaatan Teknologi Informasi Dan Komunikasi Pada Pembelajaran (Studi Kasus Pada MIN 4 Langkat) - Marinasari Fithry Hasibuan (Jurnal Analisa Pemikiran Insan Cendikia (Jurnal APIC), 2021)
This study discusses the competence of Madrasah Ibtidaiyah teachers in the use of technology and information in learning with competency indicators being the ICT training curriculum for madrasa teachers compiled by the Jakarta Education and Religious Technical Training Center. This study aims to determine the competence and problems of Islamic boarding school teachers in the use of information and communication technology in online learning during this covid 19 period. This study uses a case study with all teachers as respondents at MIN 4 Langkat. The research method used in this research is a survey method using a questionnaire that is shared via a google form. Analysis of the data used is a descriptive analysis that describes the qualifications of teacher competence in the use of ICT into four levels, namely very low, low, medium, and high. From the results of the data that has been analyzed, it was found that the competence of teachers in ICT is very low in the ability to use and utilize applications, which is 52%. Furthermore, a very low indicator is found in the experience aspect of participating in training at 57%. This shows that training activities are the most dominant factor causing the low competence of teachers in the use of ICT in learning and therefore the most effective solution to overcome them.